Tolvaptan in the Treatment of Acute Hyponatremia Associated with Acute Kidney Injury - Shilpa Gopinath; Kalyana C. Janga; Sheldon Greenberg; Shree K. Sharma (Case Reports in Nephrology)
Hyponatremia defined as a plasma sodium concentration of less than 135 mmol/L is a very common disorder, occurring in hospitalized patients. Hyponatremia often results from an increase in circulating arginine vasopressin (AVP) levels and/or increased renal sensitivity to AVP, combined with an increased intake of free water. Hyponatremia is subdivided into three groups, depending on clinical history and volume status: hypovolemic, euvolemic, and hypervolemic. Acute symptomatic hyponatremia is usually treated with hypertonic (3%) saline. Syndrome of inappropriate antidiuretic hormone hypersecretion (SIADH) and hypervolemic hyponatremia caused by heart failure or cirrhosis are treated with vasopressin antagonists (vaptans) since they increase plasma sodium (Na2+) concentration via their aquaretic effects (augmentation of free-water clearance). The role of tolvaptan in the treatment of acute hyponatremia and conversion of oliguric to nonoliguric phase of acute tubular necrosis has not been previously described.